Al-Ghazali's course in the Munqidh min al-Dalal - Muhamad Shukri, Abdul Salam (London Central Mosque Trust & The Islamic Cultural Centre, 2003)
This article analyses al-Ghazali's course and thought in his autobiographical work, al-Munqidh min al-Dalal. It argues that al-Ghazali has realised his aims in writing this famous work by elaborating the conflicts within Islamic thought in order to reform religious observance of the society after at first reforming himself.